CDL: an extensible constraints framework for model–based development. (7th July 2014) - Kreiner, Christian; Krallinger, Markus
The model–based paradigm has progressed from scientific research to industrial use. Great effort has gone into providing elaborate meta–models for different application domains, such as aviation or automotive. Instance models have to fulfil certain criteria originating from different areas, such as the development process or legal requirements, and more. These criteria are usually defined in the beginning of the development process, and often statically implemented in the tool editor. In the constraint definition framework and language (CDL) presented here, the Tool Smith can provide reusable constraints for a domain expert, who creates a custom constraints set in turn. The modeller uses these domain–specific custom constraints and applies them to the instance model he develops. Furthermore, in CDL, constraints can be augmented with actions supporting the modeller to repair defects on the model. The contribution of this work is an extensible constraint framework and language, supporting the model–based development process. A case study from the automotive domain is described, showing the feasibility of the approach.